In-depth techno-economic analysis of PV/Thermal plus ground source heat pump systems for multi-family houses in a heating dominated climate. (15th September 2019) - Sommerfeldt, Nelson; Madani, Hatef
Graphical abstract: Highlights: Parametric analysis of PVT+GSHP borehole field sizing and system controls. PVT+GSHP can save up to 89% of land needed for boreholes over GSHP. Given adequate land, PV+GSHP systems are more cost effective than PVT+GSHP systems. A multi-dimensional sensitivity analysis is made on critical economic parameters. PVT can help expand the GSHP market in land-restricted, multi-family homes. Abstract: The electrification of buildings is a promising pathway to the decarbonization of cities. This is a parametric study of the technical and economic performance of ground source heat pump (GSHP) systems with series connected solar PV/thermal (PVT) collectors. The focus is on multi-family houses (MFH) in the heating dominated climate of Sweden, where land restrictions for boreholes or noise restrictions on air heat exchangers limit the heat pump market. System efficiency and lifecycle cost results are generated using a holistic and detailed systems model in TRNSYS with 20 year simulations. The results show that PVT can reduce borehole length by 18% or spacing by 50% while maintaining an equivalent seasonal performance factor to systems without PVT. The cost for PVT+GSHP systems is higher than a traditionally designed PV+GSHP, however this does not take into account the value of the land area saved by PVT, which can be up to 89%. The reduction in land enabled by PVT has the potential to increase penetration of GSHP in MFH and promote solar energy diffusion in high latitude markets.